Former Prison and Jail Inmates’ Perceptions of Informal Methods of Control Utilized by Correctional Officers - Santos, Saskia D. (American journal of criminal justice, 2012)
Correctional officers maintain control of the institutional environment by utilizing both formal and informal methods. Although research focusing on informal methods of control is sparse, studies have indicated these methods are essential for facilities to operate efficiently. This exploratory descriptive study examined differences in former jail and prison inmate perceptions of nine methods of informal control. A limited number of the participants indicated that officers use these methods to punish or control inmates, and from their perspectives, all methods examined were viewed as being effective means of control, to some extent. Differences found between the two groups, as well as recommendations for future research are discussed.